THE GROWTH ANALYSIS OF Stichopus vastus (Echinodermata: Stichopodidae) IN KARIMUNJAWA WATERS - Bambang Sulardiono; Slamet Budi Prayitno; Ign Boedi Hendrarto (JOURNAL OF COASTAL DEVELOPMENT, 2012)
Stichopus vastus is one of sea cucumber resources utilize which has commercial economic value, locally known  as “gametes”. Because this species is continuously exploited, while the nature of life has not been known, one of them especially its growth.  Aspect of growth is an important parameter which is used as a basis for evaluating these resources, hence this resource is well managed and can be utilized in a sustainable manner. The study aims to: (1) estimates the growth characteristics mortality rate, recruitment and potential use of sea cucumber of  S.  vastus in Karimunjawa. The study is expected to give beneficial to the species of sea cucumber resource management strategy at  Karimunjawa waters, Jepara. The analysis of the growth parameters of S. vastus obtained values ​​of growth coeficient (K) of 0.55 year-1 and length infinity L ∞ value of 315.80 mm. Therefore the obtained values ​​of K tend to be close to zero value, it indicates the nature of growth tends to slow and with a relatively long life.  Life span of  S. vastus is 5.41 years, which can achieve body lengths of 283.06 to 296.91 mm, and the monthly growth rate ranged from 9.0 to 12.37 mm. The results of the analysis of mortality showed that S. vastus has value of total mortality (Z) of 0.98,  natural mortality (M) of 0.298, and catch mortality (F) of 0.682, with the rate of exploitation (E) of 0.6963. This suggests that the rate of exploitation is above the threshold standard set by the Government of 0.5 (BRKP, 2004). The analysis of the S. vastus the recruitment showed that the higest percentage recruit occurred in May-June is 17.16 - 18.33%. This is presumably due to a population increase of the spawning process in those months, although the value of the addition is not very significant.   It is suggested the need for regulations regarding: (a) the catchment season which is based on the tendency of the reproductive patterns of S. vastus, in Karimujawa, (b) restrictions on the size of the catch, (c) catch quotas, (d) the methods that are environmentally friendly catch, (e) permits the ship / boat used to catch sea cucumbers business. To support the success of regulation, it is necessary to strengthen community institutions through the management of sea cucumber resource-based society, with the Co-management approach.